The relationship between emotional intelligence and employee's job performance at Lembaga Kemajuan Kelantan Selatan (KESEDAR) Gua Musang, Kelantan: an empirical study / Siti Nadia Mazalan - Mazalan, Siti Nadia (Faculty of Business and Management, 2018)
The purpose of this study is to examine the relationship between emotional intelligence (El) which consists four components: self-awareness, self-management, social awareness and relationship management and job performance among employees in Lembaga Kemajuan Kelantan Selatan (KESEDAR), Gua Musang Kelantan. A sample of 73 employees from different departments was selected through simple random sampling. Data was collected through questionnaire survey. SPSS was used to statistical analysis and Pearson Correlation analysis was performed to determine the relationship between the independent variable (EI) and dependent variable Gob performance). Overall, the results of this study concluded that there was a statistically significant relationship between EI and job performance among employees in Lembaga Kemajuan Kelantan Selatan (KESEDAR), Gua Musang Kelantan. The results also consistent with the study done by Watkin (2002) who stated that employees with high EI have better job performance and positive interactions compared to employees with low EI.